1990
DOI: 10.3109/01485019008987585
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Parameters of Initiation and Regulation of Sperm Motility

Abstract: Studies of in vitro models demonstrate that a forward motility protein (FMP) is required for the initiation of forward motility in the immature epididymal spermatozoa. FMP is a heat-stable glycoprotein derived from epididymal plasma. During the epididymal maturation of spermatozoa in vivo, there is a marked increase of intrasperm pH and level of cyclic adenosine monophosphate (CAMP). Several studies suggest that exogenous FMP in concert with elevated intrasperm pH and level of cAMP initiates flagellar motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…Initiation of sperm motility has been associated with protein phosphorylation as well as changes in intracellular calcium and pH [7,8,25,30]. Several proteins become phosphorylated at the time sperm start moving actively [32].…”
mentioning
confidence: 99%
“…Initiation of sperm motility has been associated with protein phosphorylation as well as changes in intracellular calcium and pH [7,8,25,30]. Several proteins become phosphorylated at the time sperm start moving actively [32].…”
mentioning
confidence: 99%
“…In goat spermatozoa, the protein kinases phosphorylated only serine and threonine residues [18,22] but in addition to these residues phosphotyrosine was also detected in certain phosphoproteins of spermatozoa of mouse, rat, rabbit, boar and man [1,18,27]. In the present study, phosphoamino acid analysis of the phosphorylated acrosomal membrane proteins of hamster spermatozoa indicated that phospho-tyr was the predominant residue although phospho-ser and phospho-thr were also present in trace amounts ( Fig.…”
Section: Resultsmentioning
confidence: 73%
“…1B). Earlier studies on the intact spermatozoa of rat [19], dog [20,21], goat [22], bull [5,23] and man [16] had provided conclusive evidence for the presence of cAMP independent protein kinases in these spermatozoa, and they were also shown to be associated with the sperm plasma membrane [29,21]. Protein kinase activity in the acrosomal membranes of hamster spermatozoa was also not seen to be stimulated by cAMP or inhibited by H8 (Table 1), an inhibitor of protein kinase A, thus suggesting that in the hamster sperm acrosomal membranes the protein kinase activity was of the cAMP independent type.…”
Section: Resultsmentioning
confidence: 99%
“…[7] According to the previous studies, motility is known as one of the important parameters of qualitative evaluation of sperm cell as an impaired motility extremely affects male fertility negatively and reduces fertilization of ovules. [8] Apart from sperm motility, morphology of sperm is influenced by cytotoxic agents that target testicular tissue.…”
Section: Introductionmentioning
confidence: 99%